Analysing object-oriented application frameworks using concept analysis - Arévalo, Gabriela Beatriz (^p Datos electrónicos (1 archivo : 135 KB))
This paper proposes to use the formal technique of Concept Analysis to analyse how methods and classes in an object-oriented inheritance hierarchy are coupled by means of the inheritance and interfaces relationships. Especially for large and complex inheritance hierarchies, we believe that a formal analysis of how behaviour is reused can provide insight in how the hierarchy was built and the different relationships among the classes. To perform this analysis, we use behavioural information provided by the self sends and super sends made in each class of the hierarchy. The proposed technique allows us to identify weak spots in the inheritance hierarchy that may be improved, and to serve as guidelines for extending or customising an object-oriented application framework. As a first step, this paper reports on an initial experiment with the Magnitude hierarchy in the Smalltalk programming language.